2008
DOI: 10.1556/aagr.56.2008.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of salinity tolerance in rice ( Oryza sativa L.) genotypes at the germination and seedling stages

Abstract: The present work was conducted to study the genotypic variability of rice genotypes at the germination and seedling stages at different levels of salinity (0 M, 0.15 M, 0.2 M and 0.25 M NaCl). The results showed that increasing salinity decreased germination and seedling growth. Significant genotypic variability exists in the germination and seedling stages in response to different NaCl concentrations. Most of the genotypes showed more than 90% germination in the control, indicating good seed vigour. Two genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
3
5
0
Order By: Relevance
“…The result showed that root length decreased under salinity stress. Maiti et al (2006) found a considerable amount of genetic variation under saline condition at the seedling stage with reference to the variables such as root length, shoot and root dry weight. Roy et al (2002) reported that number of roots plant -1 decreased with the increasing levels of salinity.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The result showed that root length decreased under salinity stress. Maiti et al (2006) found a considerable amount of genetic variation under saline condition at the seedling stage with reference to the variables such as root length, shoot and root dry weight. Roy et al (2002) reported that number of roots plant -1 decreased with the increasing levels of salinity.…”
Section: Resultsmentioning
confidence: 98%
“…Islam et al (2007) also observed wide variation in phenotypes from tolerant (score 3) to highly susceptible (score 9) using modified SES of IRRI standard protocol. (Javed et al, 2006;Maiti et al, 2006). They showed that the increase in salinity level reduced the seedling height.…”
Section: Resultsmentioning
confidence: 99%
“…These five genotypes were consistently good and showed very little reduction in the traits measured under salt stress when compared to the control treatment. According to Cramer and Nowak (1992), Perez-Alfocea et al (1996), Purnendu et al (2004), Maiti et al (2006) and Janmohammadi et al (2008), salinity stress affect the roots of some genotypes more than the shoot, due to varietal differences in root capacity to exclude Na + and Cl − negative ions. At the highest salinity level (12 dS/m) there were only two mortalities (OG0315 and IR29), these genotypes were among the most affected by high concentration of salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, rice exhibits considerable intra-specific variability in resistance to salinity (Flowers and Yeo, 1981;Maiti et al, 2008).…”
Section: Introductionmentioning
confidence: 99%